INTERIM FINANCIAL REPORTING IN FUNCTION OF PROPER DECISION MAKING - Kaćanski, Slobodan; Tomašević, Stevan; Vlaović Begović, Sanja (International Journal of Economic Practice and Policy, 2014)
This paper analyses the attributes of interim financial reporting, as well as performs overview and interpretation of International Accounting Standard 34 which deals with this issue. The paper emphasizes risk and effects of interim financial statements implementation in decision making process. Time and cost limitations significantly influence the level of reliability on interim repors since those reports were not audited.